Hospital Preparedness for Critical Care during COVID-19 Pandemic: Exploratory Cross-sectional Study - Labib, John Rene; Kamal, Sally; Salem, Marwa Rashad; El Desouky, Eman D.; Mahmoud, Ahmed Taher (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The researchers conducted the study to assess intensive care units (ICUs) preparedness in Cairo University Hospitals to deal efficiently and effectively with COVID-19 upcoming waves. METHODS: An exploratory cross-sectional study was conducted at Cairo University Intensive Care Units 6 pediatric ICUs, and 2 adult ICUs in the period from the end of February to the first week of March, 2020; almost 2 weeks after the appearance of the first case of COVID-19 in Egypt by hand-delivered questionnaire method with one of the ICU staff members who were available and have time to take part in the study. WHO checklist for hospital readiness was used; this checklist based on current knowledge and available evidence on the COVID-19 pandemic for WHO’s Regional Office for the Eastern Mediterranean Region. The WHO has developed the checklist to help hospital managers prepare for COVID-19 patient management by optimizing each hospital’s capacities. The list composed of 10 key components: (1) Leadership and coordination; (2) operational support, logistics and supply management; (3) information; (4) communication; (5) human resources; (6) continuity of essential services and surge capacity; (7) rapid identification; (8) diagnosis; (9) isolation and case management; and (10) infection prevention and control. RESULTS: The overall preparedness in both pediatric and adult ICUs was 54%. Overall, adult ICUs were more prepared than pediatric ICUs, especially in communication; continuity of essential services and surge capacity; rapid identification; diagnosis; isolation; and case management. Both of them were comparable regarding operational support, logistics and supply management; human resources; and infection prevention and control, while information component was lower in both types but reached critical values 10% in adult ones. CONCLUSION: The current study demonstrated the intermediate readiness of ICUs at initial outbreak; further assessment during different phases of pandemic is required. Continues education of HCWs and active communication should be established.